2011
DOI: 10.1111/j.1447-0756.2010.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of copeptin, a novel biomarker in pre‐eclampsia

Abstract: These results suggest that increased maternal levels of copeptin may be involved in the pathogenesis of pre-eclampsia and it may be useful in the assessment of the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Copeptin and CTproET-1 did not contribute any added value in our model. So far, copeptin was investigated in just one study with PE and copeptin levels were found to increase markedly in parallel with the severity of PE when compared to women with normal, ongoing pregnancies of similar GAs in the third trimester [20] . In our study copeptin levels were also higher in the preeclamptic group (1.5-fold) but PE was not an independent determinant of higher copeptin in multivariable regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Copeptin and CTproET-1 did not contribute any added value in our model. So far, copeptin was investigated in just one study with PE and copeptin levels were found to increase markedly in parallel with the severity of PE when compared to women with normal, ongoing pregnancies of similar GAs in the third trimester [20] . In our study copeptin levels were also higher in the preeclamptic group (1.5-fold) but PE was not an independent determinant of higher copeptin in multivariable regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However the study did not provide information regarding gestational age of copeptin measurement. This was the first study to elucidate role of copeptin in PE pathogenesis and presented maternal serum level of copeptin as a marker for PE[53]. In another study assessing effect ofvaginal delivery versus caesarean delivery on maternal serum copeptin levels in pregnant women, Foda et al demonstrated increased copeptin levels in PE women compared to normotensive pregnant women.…”
mentioning
confidence: 90%
“…Another 10 blood experimental biomarkers (AT-1AA [31], calcyclin, copeptin [34], galectin-1 [36], Gas6 [37], HIF-1aOH [38], IGFALS [41], mammalian HtrA3 [45], NT-proBNP [47], and PTX3 [49]), and four urine ones (C5b-9 [33], nephrin [46], iodine [42], and prolactin [52]) had limited clinical evaluation information, which impeded the evaluation of their performance for the diagnosis of PE. No clinical data were found for the remaining nine blood markers, which consisted of adipsin, α enolase, ADMA, Ba, 2,3-BPGM, Fetal DNA, marinobufagenin, plasma UA [51], and soluble CD117.…”
Section: Resultsmentioning
confidence: 99%